Efficacy comparison of oxcarbazepine and levetiracetam monotherapy among patients with newly diagnosed focal epilepsy in China: A multicenter, open‐label, randomized study. (15th April 2022) - Zhu, Haoyue; Deng, Xuejun; Feng, Li; Lian, Yajun; Han, Xiong; Guo, Zhenli; Gou, Yulan; Du, Yuanmin; Xie, Longshan; Yao, Dongai; Liu, Yonghong; Wu, Qiang; et al.
Abstract: Aims: This multicenter, open‐label, randomized study (Registration No. ChiCTR‐OCH‐14004528) aimed to compare the efficacy and effects of oxcarbazepine (OXC) with levetiracetam (LEV) as monotherapies on patient quality of life and mental health for patients with newly diagnosed focal epilepsy from China. Methods: Patients with newly diagnosed focal epilepsy who had experienced 2 or more unprovoked seizures at greater than a 24‐h interval during the previous year were recruited. Participants were randomly assigned to the OXC group or LEV group. Efficacy, safety, quality of life, and mental health were evaluated over 12‐week and 24‐week periods. Results: In total, we recruited 271 newly diagnosed patients from 23 centers. Forty‐four patients were excluded before treatment for reasons. The rate of seizure freedom of OXC was significantly superior to that of LEV at 12 weeks and 24 weeks ( p < 0.05). The quality of life (except for the seizure worry subsection) and anxiety scale scores also showed significant differences from before to after treatment in the OXC and LEV groups. Conclusions: OXC monotherapy may be more effective than LEV monotherapy in patients with newly diagnosed focal epilepsy. Both OXC and LEV could improve the quality of life and anxiety state in adult patients with focal epilepsy. Abstract : Our study reveals 6 months of OXC monotherapy may be more effective than LEV in Chinese patients with newly diagnosed focal epilepsy. We demonstrate that early use of OXC and LEV could improve focal epilepsy patients' quality of life and anxiety state. However, two drugs may not have a significant effect on patients' depressive status in the short term.